2015
DOI: 10.2196/jmir.4897
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Prevention and Weight Loss with a Fully Automated Behavioral Intervention by Email, Web, and Mobile Phone: A Randomized Controlled Trial Among Persons with Prediabetes

Abstract: BackgroundOne-third of US adults, 86 million people, have prediabetes. Two-thirds of adults are overweight or obese and at risk for diabetes. Effective and affordable interventions are needed that can reach these 86 million, and others at high risk, to reduce their progression to diagnosed diabetes.ObjectiveThe aim was to evaluate the effectiveness of a fully automated algorithm-driven behavioral intervention for diabetes prevention, Alive-PD, delivered via the Web, Internet, mobile phone, and automated phone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
362
1
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(387 citation statements)
references
References 40 publications
(52 reference statements)
7
362
1
17
Order By: Relevance
“…Among the 22 studies, the majority were randomized controlled trials (n=13) (Ackermann et al, 2014; Azar et al, 2015; Bennett et al, 2010; Block et al, 2015; Estabrooks and Smith-Ray, 2008; Fischer et al, 2016; Fukuoka et al, 2015; Leahey et al, 2014; Ma et al, 2013; Tate et al, 2003; Thomas et al, 2015; Wing et al, 2010). Other study designs were single group intervention studies (n=5) (McTigue et al, 2009; Pagoto et al, 2015; Sepah et al, 2014; Skoyen et al, 2015; Thomas and Wing, 2013), non-randomized controlled trials (n=2) (Kramer et al, 2010; Vadheim et al, 2010), a comparative effectiveness trial (n=1) (Piatt et al, 2013), and a retrospective cohort study (n=1) (Ahrendt et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 22 studies, the majority were randomized controlled trials (n=13) (Ackermann et al, 2014; Azar et al, 2015; Bennett et al, 2010; Block et al, 2015; Estabrooks and Smith-Ray, 2008; Fischer et al, 2016; Fukuoka et al, 2015; Leahey et al, 2014; Ma et al, 2013; Tate et al, 2003; Thomas et al, 2015; Wing et al, 2010). Other study designs were single group intervention studies (n=5) (McTigue et al, 2009; Pagoto et al, 2015; Sepah et al, 2014; Skoyen et al, 2015; Thomas and Wing, 2013), non-randomized controlled trials (n=2) (Kramer et al, 2010; Vadheim et al, 2010), a comparative effectiveness trial (n=1) (Piatt et al, 2013), and a retrospective cohort study (n=1) (Ahrendt et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The methodological quality ratings ranged from 3 to 9 on a scale of 0 to 10. Thirteen of the studies were scored as ≥ 6/10 on the methodological quality scale, indicating that they had a lower risk of bias (Tate et al, 2003; Estabrooks and Smith-Ray, 2008; McTigue et al, 2009; Bennett et al, 2010; Wing et al, 2010 (study1&2); Ma et al, 2013; Ackermann et al, 2014; Leahey et al, 2014; Block et al, 2015; Fukuoka et al, 2015; Thomas et al, 2015; Fischer et al, 2016). Details of the methodological quality scoring available upon request.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these conditions (and others) are often poorly controlled. In a number of cases, automated interventions have shown health benefits: a prior study showed that a fully automated behavioral intervention leveraging Web, mobile, and automated mobile phone calls significantly improved glycemic control, body weight, and diabetes risk among prediabetics [36]; another showed that a physical activity intervention consisting of automated weekly exercise scheduling reminders, a message board to share their experience with others, and feedback on their level of physical activity increased and maintained levels of physical activity in healthy adults [37]; and another showed that a fully automated smoking cessation program using email, Web, interactive voice response, and short messaging service was associated with abstinence rates without the use of nicotine replacement therapy [38]. However, even with access to the latest technologies to monitor any biometric or condition, engagement, which leads to behavior change, is key.…”
Section: Discussionmentioning
confidence: 99%
“…Digital health tools (DHTs) have the potential to empower patients, improve access to care, enhance communication between patients and providers, improve health outcomes, and make healthcare processes and decisions more efficient and cost-effective [2][3][4][5]. DHTs are increasingly being adopted for use independently or in the context of traditional care and have been effective for monitoring and improving physical health in patients with a variety of conditions, including diabetes and cardiovascular disease [6][7][8][9]. Interest in applying digital technologies to psychiatric practice has been increasing since the early 2000s, and recommendations for future research in this area were issued in 2013 by a technical expert panel convened by the Agency for Healthcare Research and Quality and the National Institute of Mental Health [10][11][12].…”
Section: The Potential Of Digital Health Tools For Psychiatric Practicementioning
confidence: 99%